Determination of Grouper Species of Subfamily Epinephelinae from Raja Ampat (West Papua) Region Using CO1 Gene Sequence - Yanti Ariyanti; Achmad Farajallah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2019)
The Raja Ampat Islands, located near the heart of the “Coral Triangle” on Bird's Head Peninsula, West Papua, Indonesia are well known for its outstanding biological diversity and stunning marine and terrestrial habitats. Groupers (family Serranidae) has included as part of the 5 largest families associated with coral reefs on the Bird’s Head region. The grouper identification was generally done on the basis of color patterns and morphological characters, but oftentimes these characters show intraspecific variations or differences in color patterns between juvenile and adult individuals. This study aims to confirm the type of grouper species that were obtained from the sport fishing activities around Raja Ampat Island. Species confirmation from subfamily of Epinephelinae determined by analyzing the number of differences of nucleotides and genetic distance on the sequence of the CO1 gene (Cytochrome oxidase subunit 1). A total of eight fish samples were successfully sequenced and aligned. Those samples consist of eight species belonging to the three genera namely Anyperodon, Epinephelus, and Cephalopolis.